Precipitate characteristics and their effects on the mechanical properties of as-extruded Mg-Gd-Li-Y-Zn alloy. (20th October 2021) - Yu, Zijian; Xu, Xi; Mansoor, Adil; Du, Baotian; Shi, Kang; Liu, Ke; Li, Shubo; Du, Wenbo
Graphical abstract: Highlights: The TYS of the studied alloy is 295 MPa at 25℃ and 143 MPa at 200℃. Theβ1R phase is introduced in the studied alloy for the first time. Theβ1R phase forms by dislocation-assisted dynamic precipitation in hot extrusion. Theβ1R phase provides the alloy with a strong Orowan strengthening effect. Abstract: In this work, a high-performance Mg-8.4Gd-4.4Li-3.5Y-1.4Zn (wt%) alloy was successfully prepared by low-temperature hot extrusion. The studied alloy has a TYS of 295 ± 1 MPa and an EL of 2.5 %±0.2 % at room temperature, 159 ± 8 MPa and 15.9 %±1.4 % at 150 °C, and 143 ± 4 MPa and 19.8 %±1.8 % at 200 °C. The high performance at temperatures up to 200 °C is attributed to the dispersion strengthening of three Mg3 RE phase variants, the solid solution strengthening of alloying elements and the bimodal structure consisting of fine DRXed grains with random texture and coarse un-DRXed grains with basal texture. A novel island shaped β 1 R phase (FCC, a = 0.78 nm) with a size of 30 nm–100 nm is observed in the studied alloy. The β 1 R phase precipitates on the 1 1 ¯ 00 α prismatic planes. The strain-induced, dislocation-assisted dynamic precipitation during low-temperature hot extrusion is responsible for the formation of the β 1 R phase. The growth of the β 1 R phase is owing to the aid of the formation and transformation of zig-zag structures. The basal slip of < a > dislocations is the dominate deformation mechanism of the studied alloy in the early stage of tensile deformation at room temperature, while non-basal slip of < a > and < c + a > dislocations at 200 °C. Due to the strong interaction between β 1 R precipitates and dislocations, the densely distributed β 1 R precipitates significantly improve the mechanical properties via the Orowan strengthening both at room temperature and elevated temperatures.